Deskripsi Kemampuan Pemahaman Konsep Dalam Menyelesaikan Soal Geometri Berdasarkan Perbedaan Gender - Rosdiana Rosdiana; Andi Husniati; Abdul Gaffar; Andi Alim Syahri (Jurnal Bintang Pendidikan Indonesia, 2024)
This research to find out to describe the ability to understand concepts of male and female students in class VIII of SMP Negeri 3 Sungguminasa in solving geometry problems. The type of research used is describtive research with a qualitative approach. The subjects in this research was students of class VIII.D SMP Negeri 3 Sungguminasa as many as 2 students, 1 male students and 1 female students who were selected based on the data of the highest report card scores. The instrument used is a concept understanding test and interview guidelines. The results showed that there were differences in the ability to understand concepts between female students and male students with the following descriptions: (1) the ability to understand concepts of female students in the triangle material was able to meet 5 indicators of understanding the concept of interpretting, exemplifying, summarizing, inferring, comparing and not fulfilling 2 indicators of understanding the concept of classifying and explaining. (2) the concept understanding ability of male students in the triangle material is able to meet the 4 indicators of understanding the concept of interpretting, exemplifying, classifying, inferring and not meeting the 3 indicators of understanding the concept of summarizing, comparing, and explaining. Thus it can be said that female students have a better understanding of concepts than male students.